Conserving invertebrate biodiversity in agricultural and urban landscapes - Priyadarshana, Tharaka S. (Nanyang Technological University, 2025)
Agricultural intensification and urbanisation are two of the main drivers contributing to the global decline in biodiversity and ecosystem functioning. Increasing food demands make agricultural intensification inevitable, while urbanisation offers social and economic opportunities that drive people out of rural areas and into cities. The four chapters of this thesis explore these two human-modified landscapes, investigating their impacts on biodiversity and ecosystem functioning. The findings of this thesis offer practical solutions to enhance biodiversity and the ecosystem services in agriculture and urban areas without compromising their core functions.